1988
DOI: 10.1111/j.1469-8749.1988.tb04797.x
|View full text |Cite
|
Sign up to set email alerts
|

QUANTIFICATION OF CHANGES NORMAL NEONATAL EEGs WITH GESTATION FROM CONTINUOUS FIVE‐DAY RECORDINGS

Abstract: It is now possible to make a good-quality, continuous electroencephalogram (EEG) record of sick newborn babies receiving intensive care, from which seizure activity can be identified readily (Eyre et al. 1983a, b). The background EEG can be difficult to interpret, however, because it changes with increasing gestational age. In addition, there are cyclical changes in the EEG during sleep that are dependent not only on the baby's sleep state but also on the length of the preceding sleep epoch (Roffwarg et al. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…9,19,20 Anderson and associates 16 found that 60% of EEG recordings consisted of discontinuity. [21][22][23][24][25] This is sharp contrast to earlier descriptions of interburst intervals as long as 2 minutes in duration. Similar ranges for the duration of interburst intervals have been found by other authors, as listed in Table 2-1.…”
Section: Gestational Age Of Less Than 28 Weekscontrasting
confidence: 83%
“…9,19,20 Anderson and associates 16 found that 60% of EEG recordings consisted of discontinuity. [21][22][23][24][25] This is sharp contrast to earlier descriptions of interburst intervals as long as 2 minutes in duration. Similar ranges for the duration of interburst intervals have been found by other authors, as listed in Table 2-1.…”
Section: Gestational Age Of Less Than 28 Weekscontrasting
confidence: 83%
“…Previous neonatal sleep studies initially applied automated techniques to assess functional brain maturation, using analyses that were based on assumptions of linearity, without consideration of time-dependent changes (Havlicek et al, 1975;Giaquinto et al, 1977;Sterman et al, 1977;Lombroso, 1979;Willekens et al, 1984;Connell et al, 1987;Bes et al, 1988;Eyre et al, 1988; Kuks et al, 1988). The preferred methodological approach has been fast Fourier transform analyses, studied initially with full-term neonates (Ktonas et al, 1995;Witte et al, 1997;Lehtonen et al, 1998;Eiselt et al, 2001;Field et al, 2002), followed by more recent reports in preterm infants (Sawaguchi et al, 1996;Eiselt et al, 1997;Myers et al, 1997;Holthausen et al, 2000;Schramm et al, 2000;Kuhle et al, 2001;Vanhatalo et al, 2002).…”
Section: Ms Schermentioning
confidence: 99%
“…These investigators found a decrease in discontinuous activity from 27% at 28 weeks GA to 10% at 38 weeks. Eyre et al [22] also investigated first week EEG recordings and found a decrease in discontinuity from 35% at 28 weeks GA to 10% at 36 weeks. However, both authors used different definitions of discontinuous EEG activity and definitions were not quantitative, making this technique difficult to reproduce.…”
Section: Lma and Dc-% As Quantitative Parametersmentioning
confidence: 99%